PEMAKAIAN BAHASA OLEH MASYARAKAT BUGIS DI DESA SENGANAN, TABANAN, BALI - I Made Suparta; I Nyoman Kardana (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
[Title: The language use by Bigesnese community at Senganan Village, Tabanan, Bali] This research is about language use by the Bugisnese community at Senganan Village, Penebel District, Tabanan as a minority ethnic group in Bali. The research discusses the use of languages among the different domains and factors causing the language shift at Senganan Village. Theory used in this research is the theory of bilingualism, the theory of language choice and the theory of language shift. The result shows that the use of Bugisness language is not found on different observed domains, such as domains family, religion, neighborhood, administration, and education. The use of Balinese and Indonesian dominated their language uses in all domains. Thus, it can be concluded that Bugisnese language is not used anymore by the community or its use has already shifted. The factors causing the shift of Bugisnese language at the village is internally related to the attitude of the speakers covering unsustainable transfer of the mother tongue and the unfaithfulness to the mother tongue, and externally it deals with the factor consisting of geographic environment of the village surrounded by villages of which people mostly speak Balinese language.